Simulation of ferro-alloy smelting in DC arc furnaces using Pyrosim and FactSage. (December 2016) - Jones, Rodney T.; Erwee, Markus W.
Abstract: Mintek has applied DC arc furnace technology to the reductive smelting of numerous materials over more than three decades. The first industrial implementation of this technology was for the smelting of chromite fines to produce ferrochromium in 1984. Since 1985, process simulation has been carried out using Pyrosim and FactSage software to study this process. Some examples are presented of the mass and energy balances and thermodynamic calculations used for the steady-state simulation of chromite smelting for the production of ferrochromium. There is a place for equilibrium calculations involving non-ideal slag and alloy solutions, as well as for empirical models that can be used in an operating plant environment. Highlights: DC arc furnaces have been used for ferrochromium production for over 30 years. FeCr production process has been simulated using Pyrosim and FactSage since 1985. Mass and energy balances for FeCr production are presented. Both equilibrium calculations and empirical models are useful in plant operations.